Single-center study of Lynch syndrome screening in colorectal polyps - FangChao Zhu; Da Pan; Hui Zhang; Qiong Ye; PeiSong Xu; Jie Pan (Hereditary Cancer in Clinical Practice, 2019)
Abstract Background Lynch syndrome is the most common hereditary colorectal cancer syndrome, and adenoma is one of the important premalignant lesions to colorectal cancer in Lynch syndrome. The first objective of this study was to calculate the detection rate of Lynch syndrome in colorectal polyps by using mismatch repair immunohistochemistry as the initial screening strategy. The second objective of this study was to optimize screening strategies for adenoma associated with Lynch syndrome by integrating polyp and/or patient characteristics such as polyp size, location, dysplasia, age of onset and/or family history of cancer. Methods From June 2014 to May 2016, immunohistochemistry was performed for mismatch repair proteins (MLH1, MSH2, MSH6, and PMS2) using endoscopically resected specimens obtained from newly diagnosed colorectal adenomas. Gene analysis was performed in patients with missing expression of mismatched repair protein. Results Five hundred and ten patients underwent colorectal polyp resection, with a total of 718 polyps. Five hundred and eight resected adenomas underwent mismatch repair protein immunohistochemical testing. Loss of mismatch repair protein expression was observed in six adenomas, accounting for 1.18% of all adenomas. Five patients then underwent genetic tests to identify two pathogenic mutations from different individuals, while another patient was suspected to have a pathogenic mutation. Three patients were younger than 50 years old. Two patients had advanced histology (high-grade dysplasia and malignant components) and one patient had a family history of cancer. Conclusion Immunohistochemical detection of colorectal polyp mismatch repair protein as Lynch syndrome screening efficiency is low. Effective screening strategies may be improved by optimizing patient/polyp selection, such as focusing on young adenoma patients with a family history of cancer, or patients who present with high-risk features (large size, villous, high-grade dysplasia and malignant components).